Availability And Quality Of Denpasar City Regional Pedestrian Paths As An Effort To Improve Bali Tourism - Mahayani, Ni Komang Indra; Warnata, I Nyoman; Meila Utami, Putu Padma Sthri (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2023)
Creating a compact and pedestrian-friendly city, some urban areas require land that is structured so that it is easily accessible, so that pedestrians can find their destination while walking. A phenomenon that is often found is misuse of the function of pedestrian facilities. Misuse of pedestrian facilities is a frequent problem. One of the quickest methods to solve this problem is to have accessibility for pedestrians. This can increase the attractiveness of a city that provides facilities for residents and tourists to carry out activities. The aim of this research is to identify the quality and availability of pedestrian paths desired by users. Using quantitative methods by distributing questionnaires randomly, data analysis techniques are descriptive statistical analysis. The results of this research conclude that the Denpasar City area has different criteria regarding the quality and availability of desired pedestrian paths. Pedestrian path users hope to make the city pedestrian-friendly and should be designed with wide pedestrian dimensions. Making a pedestrian-friendly city requires attention to safety, beauty and pedestrian amenities. This illustrates that there is no walkable city that users want in Denpasar City. Further research is looking for places in Denpasar City that are suitable for walking for residents and tourists.